Mitral Valve Obstruction and Pulmonary Hypertension Caused by a Giant Left Atrial Myxoma Prolapsing in the Left Ventricle - Musuraca Gerardo; Agostoni Pierfrancesco; Boldi Emiliano; Terraneo Clotilde; Imperadore Ferdinando; Del Greco Maurizio (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2015)
Atrial myxomas are the most common primary cardiac tumors to diagnose. They are benign and have variable presentation. They have an excellent prognosis following surgical excision. We report a case of a 60 year old female who presented with initial signs of both right and left heart failure, fever and cough. Auscultation of the heart revealed an apical mid diastolic murmur. Trans-thoracic and transesophageal echocardiography revealed a pedunculated, giant left atrial myxoma that prolapsed through the mitral valve into the left ventricle in diastole producing functional mitral valve stenosis. The patient underwent a successful surgical excision of the tumor. The diagnosis and management of atrial myxomas is here reviewed.